Ancaman Obesitas Maternal terhadap Kejadian Stunting Anak - Mayditania Intan Bunga Pratiwi; Dwiana Ocviyanti; Luh Ade Ari Wiradnyani; Rima Irwinda (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
In recent decades, the world has faced a dual challenge in nutritional health: the rising rates of maternal obesity and the high prevalence of stunting in children. Data from the World Health Organization in 2022 revealed that over 2.5 billion adults were overweight or obese, with 44% of them being women. This condition occurs not only in high-income countries but also in low- and middle-income nations. National surveys indicate that the prevalence of obesity among adult women (over 18 years old) has increased from 29.3% (Basic Health Survey 2018) to 31.2% (Indonesian Health Survey 2023).